2008
DOI: 10.1208/s12248-008-9015-x
|View full text |Cite
|
Sign up to set email alerts
|

Highly Variable Drugs: Observations from Bioequivalence Data Submitted to the FDA for New Generic Drug Applications

Abstract: Introduction. It is widely believed that acceptable bioequivalence studies of drugs with high withinsubject pharmacokinetic variability must enroll higher numbers of subjects than studies of drugs with lower variability. We studied the scope of this issue within US generic drug regulatory submissions. Materials and Methods. We collected data from all in vivo bioequivalence studies reviewed at FDA's Office of Generic Drugs (OGD) from [2003][2004][2005]. We used the ANOVA root mean square error (RMSE) from bioeq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
0
16

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(135 citation statements)
references
References 5 publications
4
115
0
16
Order By: Relevance
“…For example, in a two-way crossover design, two products with identical bioavailability may require 40 subjects to demonstrate BE with 90% power if the intra-subject variability is 30% but the number of subjects increases to approximately 140 at intra-subject variability of 60% (26). Similar analysis of BE data by Food and Drug Administration (FDA) for new generic drug applications showed that generally studies of highly variable drugs (root mean square error (RMSE)≥0.3) used more subjects than BE studies of drugs with lower variability (RMSE<0.3) (27). For drugs that had high variability in C max , the number of study subjects ranged from 18 to 134, with an average of 46 subjects per study.…”
Section: Highly Variable Drugsmentioning
confidence: 98%
“…For example, in a two-way crossover design, two products with identical bioavailability may require 40 subjects to demonstrate BE with 90% power if the intra-subject variability is 30% but the number of subjects increases to approximately 140 at intra-subject variability of 60% (26). Similar analysis of BE data by Food and Drug Administration (FDA) for new generic drug applications showed that generally studies of highly variable drugs (root mean square error (RMSE)≥0.3) used more subjects than BE studies of drugs with lower variability (RMSE<0.3) (27). For drugs that had high variability in C max , the number of study subjects ranged from 18 to 134, with an average of 46 subjects per study.…”
Section: Highly Variable Drugsmentioning
confidence: 98%
“…(FDA) discussed two approaches acceptable to the FDA for bioequivalence studies of highly variable generic drug products (21). The first is the reference-scaled average bioequivalence approach, whereby the BE acceptance limits are scaled to the variability of the reference product.…”
Section: Hvd: Reference-scaled Average Bioequivalence and Sequential mentioning
confidence: 99%
“…Using this BCS approach, a highly permeable, highly soluble drug substance formulated into a rapidly dissolving drug product may need only in vitro dissolution studies to establish BE. 20 In addition, in vitro approaches to document BE for nonbioproblem drugs approved before 1962 remain acceptable as per FDA regulations. Dissolution tests can also be used to reduce the number of in vivo studies in other circumstances, and to i) assess batch-to-batch quality and support batch release; ii) provide process control and quality assurance; and iii) assess the need for further BE studies relative to minor post-approval changes, where they function as a signal of bioinequivalence.…”
Section: 28mentioning
confidence: 99%
“…Dissolution tests can also be used to reduce the number of in vivo studies in other circumstances, and to i) assess batch-to-batch quality and support batch release; ii) provide process control and quality assurance; and iii) assess the need for further BE studies relative to minor post-approval changes, where they function as a signal of bioinequivalence. 20 The broad spectrum of BA/BE in vitro studies specifications were provided by each regulatory authority.…”
Section: 28mentioning
confidence: 99%
See 1 more Smart Citation